Research on the Innovation of Teaching Mode of Transportation Course in Colleges and Universities under the Background of Artificial Intelligence - Zhang, Yexin (Education Insights, 2026)
Into the systems of the transportation industry, against the backcloth of a new undulation of technical revolution and industrial transformation, technology such as tidings, big information. And digital twins are rapidly incorporate, push the changeover from experience-found management to information-repel and reasoning conclusion-produce framework, hence the technological furtherance in this sphere has parent the bar for cultivating transportation professionals. The traditional teaching model-preponderantly hypothesis-ground, with bounds and evaluation methods-now flunk to fill the requirement of the transportation era for versatile gift. Under the setting of hokey word, in sparkle of this, this composition conducts a discipline on the innovation of teaching models for transportation courses in higher education.